The epistemological foundation of quantitative and qualitative research methodologies a critical analysis - Ali, Muhammad Mumtaz (Probe & Find Forum Lahore, Pakistan, 2020)
There is an assumption in the discourse on research methodologies of social sciences and religious studies that the quantitative and qualitative research methodologies are neutral and universally acceptable as valid methods of research. Hence, they are studied extensively and applied in both pure and applied research programs without reservation especially in social sciences and religious studies. This paper examines critically the epistemological foundation of quantitative and qualitative research methodologies to ascertain the validity of this assumption. For this, the paper explores the epistemological foundation of quantitative and qualitative research methods. It is followed by an examination of the epistemological foundation of research methodologies of modern research. Finally, the paper assesses how for the application of these methodologies is relevant to Islamic tradition especially to Islamic research